Architecture of dwarf shrubs and dwarf subshrubs of the genus of Thymus L. and Scutellaria L. (Lamiaceae) - Cheryomushkina Vera (EDP Sciences, 2021)
The structure of 24 species of Thymus and 12 species of Scutellaria was studied using the architectural approach. For the first time, an architectural unit was described, it is a branched sympodial axis. The architectural unit consists of sympodial axes n+1 order, formation shoots, branching shoots, ephemerous shoots. The wide distribution of species and development of species in contrasting habitat conditions is due to the diversity of sympodial axes and shoots that are part of the architectural unit. Depending on the type of branching and the spatial position of sympodial axes, six modifications of architectural unit were identified. It is established that the structure of mature individuals are formed due to the repetition one of the same modification of architectural unit or a combination different modifications of architectural unit. Each of the variants of the combination determines the type of life form (dwarf shrub or dwarf subshrub) and biomorph (monocentric, dense polycentric, sparse polycentric) and depends on the conditions of the ecotope. The identified modifications of the architectural unit and the variants of their combination determine the strategy for the development of dwarf shrubs and dwarf subshrubs in the development of Northern and Central Asia.